Dynamic and fluctuating generation of hydrogen peroxide via photorespiratory metabolic channeling in plants. (30th November 2022) - Li, Xiangyang; Liao, Mengmeng; Huang, Jiayu; Chen, Linru; Huang, Haiyin; Wu, Kaixin; Pan, Qing; Zhang, Zhisheng; Peng, Xinxiang
SUMMARY: The homeostasis of hydrogen peroxide (H2 O2 ), a key regulator of basic biological processes, is a result of the cooperation between its generation and scavenging. However, the mechanistic basis of this balance is not fully understood. We previously proposed that the interaction between glycolate oxidase (GLO) and catalase (CAT) may serve as a molecular switch that modulates H2 O2 levels in plants. In this study, we demonstrate that the GLO–CAT complex in plants exists in different states, which are dynamically interchangeable in response to various stimuli, typically salicylic acid (SA), at the whole‐plant level. More crucially, changes in the state of the complex were found to be closely linked to peroxisomal H2 O2 fluctuations, which were independent of the membrane‐associated NADPH oxidase. Furthermore, evidence suggested that H2 O2 channeling occurred even in vitro when GLO and CAT worked cooperatively. These results demonstrate that dynamic changes in H2 O2 levels are physically created via photorespiratory metabolic channeling in plants, and that such H2 O2 fluctuations may serve as signals that are mechanistically involved in the known functions of photorespiratory H2 O2 . In addition, our study also revealed a new way for SA to communicate with H2 O2 in plants. Significance Statement: It was found that the complex of glycolate oxidase (GLO) and catalase (CAT) exists in different states, which are dynamically interchangeable in response to various stimuli, typically SA, at the whole‐plant level. Changes in the states of the complex were found to be closely linked to peroxisomal H2 O2 fluctuations. The study unveils a physical way for the regulation of ROS homeostasis via photorespiratory metabolic channeling, and a new mechanism for SA–H2 O2 communication in plants.